2011
DOI: 10.1213/ane.0b013e31822c9679
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Noninvasive Hemoglobin Measurement by Multiwavelength Pulse Oximetry After Cardiac Surgery

Abstract: Our study demonstrates poor correlation between hemoglobin measured noninvasively by multiwavelength pulse oximetry and a laboratory hematology analyzer. The difference was greater when the pulse oximetry perfusion index was low, as may occur in shock, hypothermia, or vasoconstriction patients. The multiwavelength pulse oximetry is not sufficiently accurate for clinical use in a cardiovascular intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…In addition, the number of blood samples and time needed to obtain Hb values can be reduced. Previous studies have demonstrated that SpHb was accurate when compared with laboratory haemoglobin measurements in relatively stable clinical situations [1][2][3] but not in critical situations when Hb data are frequently needed, such as after cardiac surgery [7] or when there is inadequate perfusion [8]. Therefore, whether or not SpHb is sufficiently accurate has been controversial in the peri-operative period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the number of blood samples and time needed to obtain Hb values can be reduced. Previous studies have demonstrated that SpHb was accurate when compared with laboratory haemoglobin measurements in relatively stable clinical situations [1][2][3] but not in critical situations when Hb data are frequently needed, such as after cardiac surgery [7] or when there is inadequate perfusion [8]. Therefore, whether or not SpHb is sufficiently accurate has been controversial in the peri-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether or not SpHb is sufficiently accurate has been controversial in the peri-operative period. It had been hoped that the sensors would be revised or another solution would be developed [4][5][6][7][8]. Our simple in-vivo adjustment method may help resolve some of the issues with sensors and further develop the efficacy of SpHb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy and reliability of the portable Pronto-7 Pulse COOximeter was reported in numerous studies conducted in the operating room [10][11][12][13][14][15][16][17][18][19][20][21] and in the intensive care unit [4,5,[22][23][24][25] with predominantly satisfactory performance. In a study done in bleeding trauma patients the agreement was moderate [bias (LOA) of -0.6 (-3.0; +1.9)] g/dl [26], where the limit of agreement is defined as the mean difference + twice the standard deviation of the differences [27].…”
Section: Discussionmentioning
confidence: 99%
“…About 58 % of their data pairs had a difference [1 g/dL, and [32 % had a difference [2 g/dL [30]. Another report on 41 cardiac ICU patients showed a poor correlation and wide LOA between SpHb (Radical-7) and tHb [31]. Additionally, 40 % of the patients received norepinephrine.…”
Section: Icumentioning
confidence: 99%